An unusual interpodocyte cell junction and its appearance in a transplant graft kidney. Issue 2 (February 1988) - Harrison, D J; Jenkins, D; Dick, J
Abstract : In a case of focal and segmental glomerulonephritis unusual cell junctions were discovered between podocytes. These most closely resembled lesions described in aminonucleoside induced nephrosis in rats and were unlike anything previously seen in our experience. Shortly after renal transplantation nephrotic syndrome recurred and biopsy specimens showed recurrent focal and segmental glomerulonephritis, with the appearance of these unusual interpodocyte junctions in the graft kidney. This may be related to circulating factors in the blood of the patient.